Penalty points as a tool for reducing road traffic injuries: international experience and prospects for implementation in the Republic of Kazakhstan - Kulzhanov А.Е.; Tazhenov А.Д.; Baikenzheyev А.С. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
This article examines the problem of improving the effectiveness of administrative enforcement in the field of road traffic safety in the Republic of Kazakhstan. Based on the analysis of official statistics, it is established that the current system, primarily based on monetary fines, does not provide a sufficient preventive effect, especially for repeat offenders. The aim of the study is to conduct a comparative analysis of international experience with demerit point systems and to develop scientifically grounded proposals for their implementation in Kazakhstan. The methodological framework includes comparative legal, statistical, systemic, and formal legal methods. The study analyzes demerit point systems in Germany, France, Italy, as well as in Uzbekistan and Ukraine, which made it possible to identify common principles such as accumulation, inevitability of consequences, differentiation of offenses, and the presence of positive incentive mechanisms. As a result, a conceptual model of a demerit point system adapted to the conditions of Kazakhstan is proposed. The model includes integration with the national eGovernment platform, a differentiated scoring system depending on the severity of violations, incentive mechanisms for safe driving, and a staged system of impact on offenders. The scientific novelty lies in the development of a comprehensive model aimed at shifting from a punitive-fiscal approach to an educational and preventive paradigm in road safety enforcement. The implementation of the proposed system will enhance the effectiveness of prevention, reduce road traffic injuries, and strengthen public safety.